Coercion and interpretation (Società e diritti, 2019)
Coercion and interpretation is the theme to which the sages of the first issue of the journal SeD are devoted and is the subject analyzed in this paper, where the Author confront the classic essay by Pierre Bourdieu "The strength of Law" and the namesake book by Frederick Schauer. The matter “interpretation of law” is also the subject of insights from a recent essay by Alessandro Catelani which, like that of Roberto Bin, open new perspectives for research, especially in the socio-legal field. Key words: Justice, Legitimation, Interpretation of law